(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Digital transformation has become a strategic element in strengthening competitiveness and expanding the market reach of local products in rural areas. This community service research aims to empower 22 sugarcane farmers in Nagari Lawang, Agam Regency, through participatory digital marketing strategy training integrated with the use of social media and e-commerce. The program involves four stages of activities, namely socialization, practice-based training, implementation assistance, and continuous evaluation. Participants were trained to manage business accounts on Facebook, Instagram, and TikTok, as well as online stores on Shopee and Tokopedia, accompanied by the development of the "Saka Lawang Digital Market" community website as a collective promotion center. The results showed an 83% increase in digital literacy, the opening of 18 active business accounts on social media, 15 new online stores on the marketplace, and a 20-35% increase in sales turnover for the majority of participants. These findings confirm that community-based rural digitalization can drive local economic innovation, strengthen inclusive workforce structures, and expand community participation in the digital creative industry ecosystem. Additionally, this program makes a tangible contribution to the sustainable development agenda by supporting equitable economic growth and strengthening innovation-based infrastructure at the community level.